Ilmu Dalam Perspektif Imam Al-Ghazali - Mubarok, Muhammad Fadhlulloh (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract Science is the obligation of muslims to open the horizons of the islamic world yag rooted in the revelation of the Qur'an and the Sunnah, supported by akaluntuk the development of Islamic education. The islamic life is very closely connected with education, in order to continue generasa young intellect and know religion. A figure of islam Al-Imam Al-Ghazali is an expert philosopher famous with his work we Ihya; Ulumuddin (reviving the knowledge of religion). In the book of Ihya ‘Ulumuddin explained about the concept of science that can be drawn as a reference of scientific a muslim. in the works of Al-Ghazali explained in detail about the meaning of the concept of science which is very important for the development of islamic religious education. Al-Ghazali divides knowledge into two categories, namely: fardhu ‘ain and fardhu kifayah. Therefore, the concept of education should be started from the fard ‘ain fardhu kifayah. Keywords: Of Science, Imam Al-Ghazali, Fard ‘Ain, Fard Kifayah. Abstrak Ilmu merupakan kewajiban muslim untuk membuka cakrawala dunia islam yag bersumber pada wahyu Al-Qur’an dan Sunnah dengan didukung oleh akaluntuk perkembangan pendidikan Islam. Kehidupan islam sangat erat hubungannya dengan pendidikan, demi meneruskan generasa muda yang intelek dan tahu agama. Seorang tokoh islam Al-Imam Al-Ghazali merupakan ahli filosof masyhur dengan karyanya kita Ihya; Ulumuddin (menghidupkan kembali pengetahuan agama). Dalam kitab Ihya ‘Ulumuddin dijelaskan tentang konsep keilmuan yang dapat ditarik sebagai rujukan ilmiah seorang muslim. dalam karya Al-Ghazali dijelaskan secara detail tentang makna konsep keilmuan yang sangat penting demi perkembangan pendidikan agama islam. Al-Ghazali membagi ilmu menjadi dua kategori yaitu: fardhu ‘ain dan fardhu kifayah. Oleh karena itu, konsep pendidikan seharusnya dimulai dari yang fardhu ‘ain untuk fardhu kifayah. Kata Kunci: Ilmu, Imam Al-Ghazali, Fardhu ‘Ain, Fardhu Kifayah.